Relationship between Platelet Count and Volume and Spontaneous and Pharmacological Closure of Ductus Arteriosus in Preterm Infants - Dani, Carlo; Poggi, Chiara; Fontanelli, Giulia (American Journal of Perinatology, 2013)
It has been reported that low platelet count may increase the risk of patent ductus arteriosus (PDA) in preterm infants. Moreover, high mean platelet volume (MPV) has been found to be associated with the development of prematurity complications due to enhanced platelet reactivity. Our aim was to assess the relationship between platelet count and MPV and the occurrence of PDA and its resistance to ibuprofen closure in a cohort of extremely preterm infants. Platelet count <100 (×103/mm3; odds ratio 4.50; 95% confidence limits 1.39 to 14.61) at birth is an independent risk factor for PDA but does not affect its response to ibuprofen. MPV values did not influence PDA fate. Low platelet count increases the risk of developing a hemodynamically significant PDA but does not affect the ibuprofen closure rate. MPV is unrelated to the DA outcome.
Keywords: platelet count; platelet volume; ductus arteriosus; preterm infant